1983
DOI: 10.1093/ajcp/80.2.140
|View full text |Cite
|
Sign up to set email alerts
|

Evidence to Suggest that the Human Fetal Spleen Is Not a Hematopoietic Organ*

Abstract: The human fetal spleen commonly is regarded as an organ of hematopoiesis. Because of the authors' interest in myelofibrosis with myeloid metaplasia (MMM) and because the myeloid metaplasia commonly is regarded as a reactivation of embryonic sites of blood formation, spleens from 48 fetuses and stillborn infants were studied, in an attempt to evaluate splenic hematopoiesis (myelopoiesis). The authors employed immunohistologic and cytochemical technics to identify granulocytic, erythroid, and megakaryocytic cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In accordance with previous publications by others (Wilkins et al 1994;Wolf et al 1983), we did not observe hematopoietic clusters or megakaryocytes in the red pulp of fetal spleens. Nucleated red cells were present outside vessels at stage 0 and later, but these cells were not arranged in clusters and seemed to have travelled to the spleen via the circulation.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with previous publications by others (Wilkins et al 1994;Wolf et al 1983), we did not observe hematopoietic clusters or megakaryocytes in the red pulp of fetal spleens. Nucleated red cells were present outside vessels at stage 0 and later, but these cells were not arranged in clusters and seemed to have travelled to the spleen via the circulation.…”
Section: Discussionsupporting
confidence: 94%
“…We must conclude that hemopoiesis does not develop in the spleen of the human embryo and fetus. The same conclusion has been reached by a few investigators (AMANO,1948;KELEMEN, CALVO and FLIEDNER, 1979;WOLF, LUEVANO and NEIMAN, 1983).. WOLF and associates (1983) asserted that hemopoietic cells in the fetal spleen were those filtered out from the fetal blood. We agree with them in this context.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, however, a few investigators have reported that the spleen was not a significant organ of hemopoiesis in the human fetus (KELEMEN, CALVO and FLIEDNER, 1979;WOLF, LUEVANO and NEIMAN, 1983). Attention was focused on this problem in the present study on the ultrastructures of hemopoietic cells and reticular cells in the human fetal spleen.…”
Section: Discussionmentioning
confidence: 83%
“…They argued against the neoplastic theory because EMH "lacks the destructive proliferation of immature forms of a single cell line characteristic for leukemia" [2]. They also disputed the compensatory theory as they observed EMH in patients with markedly hypercellular BM and lack of correlation between the degree of medullary fibrosis and splenic weight or degree of EMH [2,3]. Wolf and Neiman therefore proposed a new explanation for EMH.…”
Section: Introductionmentioning
confidence: 99%